A Constitutive Model for Plain Concrete Subjected to Static Loading - Tavio Tavio (IPTEK The Journal for Technology and Science, 2007)
A numerical model based on the new theoretical micromechanical and lattice models has been proposed to simulate the fracture behavior of concrete specimens. The numerical model has been developed to implement the proposed theoretical micromechanical model using finite element method which employing the lattice model. Using the program developed, the numerical model has been used to simulate concrete specimens under direct tension and bending load conditions. Close agreement between the numerical results and the experimental data in literature indicated that the model is reasonably good, even in predicting the crack development. The numerical lattice model can, therefore, be an effective and useful tool for the analysis of the micro-structural behavior of concrete and for the design of concrete structures.